ECONOMIC AND SOCIO-CULTURAL POTENTIAL IN ROWING SPORT COACHING PROGRAM AT TANJUNG JABUNG DISTRICT, JAMBI PROVINCE - Widowati, Atri; Rohendi, Tjetjep; -, Soegiyanto (The Journal of Educational Development, 2015)
The purpose of this study is to identify, understand, explain, and find the patterns and principles of: (1)economic and socio-culturalpotential of rowing sport activities, (2)rowing sportplanning and its social development, (3) organizing of rowing sport coaching program as an effort to make it asachievement sport achievement, (4) implementation of rowing sport coaching program as an attempt to make it as an achievement sport, (5) control of rowing sport coaching program as an effort to make is as achievement sport. This study employed qualitative approach. The technique of data collection was carried out through observation, interviews, and documentation. The data was further analyzed interactively through some stages namely data collection, data reduction, data presentation, and data verification. The result of research shows that (1) the economic and socio-culturalpotentialplays an important role in sports development, (2) planning as an effort of rowing sport coaching program is conducted through the establishment of training programs by the coaches who are in charge of the athletes and the determination of strategic plan by the youth and sport programsdivision,in the Department of Culture, Tourism, Youth, and Sport, (3) organizing the rowing sports coaching program is conducted through clearly dividing the duties, authorities, and responsibilities among athletes and coaches, (4) implementation of rowingÂ  sport coaching program is conducted through the implementation of a training program that has been set by coach based on schedule, (5)the control of rowing sport coaching program is conducted by carrying out the tests and measurements regularly for the athletes once to twice a month, organizing competitions, and involving athletes in the championship both in the national and international levels. The conclusion of this researchshows that there is a strong inter-relationship between economic and socio-culturalpotential toward rowing sport coaching program in Tanjung Jabung District, Jambi. This study proves that the coaching program should be directed and it should considerall the potential in the area. Therefore, the mapping of the sport in the regions and national-wide will be on the right target.